Conflict Management Model of Financial Accounting System: Applicated in Semarang Regional Government - Saifudin, Saifudin; Ardiani, Sulistyawati Ika (Economics and Business Solutions Journal, 2020)
The purpose of this study was to determine the effect of organizational behavioral factors, cognitive and affective conflict against regional financial accounting system usefulness and behavioral factors influence the organization of cognitive and affective conflict and behavioral factors influence the organization of the usefulness regional financial accounting system intervening by the presence of cognitive and affective conflict. The influence of behavior factors were superiors support, clarity of purpose and training. The study was conducted at the sub-district and department employees in Semarang. The population is some sub-district and department employees who work on the financial section. Analysis of the data in this research was using Partial Least Square (PLS) method. The results of this study indicate a positive influence of organizational factors on the usability of Regional Financial Accounting System and cognitive conflict and there is a positive effect of cognitive conflict with usability Regional Financial Accounting System. Organizational factors negatively affect affective conflict and affective conflict negatively affects the usefulness of Regional Financial Accounting System.